Sensing the Polycrisis - Mari Keski-Korsu (Suomen Antropologi)
This study investigates sensory experience whilst walking in the era of the polycrisis. Through a walk followed by an interview, an attempt to gather impressions about sensory experiences and ponder how these sensory impressions reflect relations within the environment by placing them alongside environmental data, and describe the implications of the polycrisis. The focus lies on sensory registers related to the environment in the Arctic village of Abisko in northern Sweden, an area that is changing rapidly and which has been extensively researched within the natural sciences. The study draws on artistic research and the concept of transcorporeality—that is, bodies are in relation with the world around them and in a constant state of becoming with it. Transcorporeality as a concept is applied as walking ritualisation using multisensory ethnography and ‘walking with’ methodologies to investigate the sensory experiences and relations that make them. The interlocutors—here, called participants—were permanent residents of Abisko. I argue that a walking ritualisation, which involves repetitive sensing and a transcorporeal experience of the environment, adds to the narrative and knowledge of the Arctic polycrisis. In essence, that ritualisation may enmesh the human subject in the more-than-human world.